Assets and Liabilities: When Do They Exist? - Cade, Nicole L.; Koonce, Lisa; Mendoza, Kim I.; Rees, Lynn; Tokar, Mary B. (Contemporary Accounting Research, 2019)
ABSTRACT In this paper, we investigate whether the current references to probability in standard setters' conceptual definitions of assets and liabilities cause individuals to believe that the probability of a future transfer of economic benefits must be above some meaningful threshold for an asset or a liability to exist—a belief that is contrary to standard setters' intent. Results of multiple experiments indicate that the majority of individuals do use a high probability threshold to determine asset existence, whereas for liabilities the majority use a very low threshold. Thus, even under ceteris paribus conditions, liabilities are more frequently judged to exist than assets—a phenomenon analogous to accounting conservatism, as has been discussed in terms of the performance statement. These findings are robust to variation in formal training and in type of liability, and cannot be explained by alternative approaches to judging existence. Consistent with standard setters' intentions, results also suggest that their proposed changes to the definitions of assets and liabilities—changes that attempt to clarify the intended role of probability—do cause a greater proportion of participants to indicate that the relevant financial statement element (asset or liability) exists, relative to participants with no definition. Our study provides important insights for standard setters as they continue work on their missions to update their Conceptual Frameworks and for researchers regarding the role of conservatism on the balance sheet.